Analisis Kebutuhan Pengembangan Instrumen Penilaian Kinerja Karyawan CV Jetindo Niaga Utama Menggunakan Metode 360 Derajat Berbasis Website - Febriana, Suci Wulan; Lestari, Wahyu; Supriyadi, Supriyadi (Jurnal Manajemen, 2022)
Needs analysis is a study whose information serves as the basis for developing a particular product. Researchers will collect information and data related to the development of employee assessment instruments through needs analysis. Employee performance assessment is one of the important indicators of the quality of the human resources department of an organization or company. This research uses descriptive methods with a qualitative approach. The subject of the study is the need for the development of employee assessment instruments CV Jetindo Niaga Utama, Semarang city, while the object of research is all employees from CV Jetindo Niaga Utama. Results from this research is, 1) the need for the development of employee assessment instruments using a website-based 360-degree method, and 2) factors that support and hinder the analysis of the need for the development of employee assessment instruments using a website-based 360-degree method. Based on the results of the needs analysis, almost all employees argue that the need to develop assessment instruments, indicated that 59% of employees answered in dire need of instrument development and 38% chose to require instrument development.. The results of this research will be used as a research basis for the development of CV Jetindo Niaga Utama employee assessment instruments using a website-based 360-degree method